2022
DOI: 10.3390/molecules27030780
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Effect of Heat Treatment on the Spectral Pattern of Unifloral Honeys Using Aquaphotomics

Abstract: In this study we aimed to investigate the effect of heat treatment on the spectral pattern of honey using near infrared spectroscopy (NIRS). For the research, sunflower, bastard indigo, and acacia honeys were collected from entrusted beekeepers. The honeys were not subject to any treatment before. Samples were treated at 40 °C, 60 °C, 80 °C, and 100 °C for 60, 120, 180, and 240 min. This resulted in 17 levels, including the untreated control samples. The 5-hydroxymethylfurfural (HMF) content of the honeys was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
2
7
0
Order By: Relevance
“…Additionally, the highest HMF content in honey samples was obtained in those samples subjected to more severe and prolonged heat treatments. Similar findings were also reported by Bodor et al [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, the highest HMF content in honey samples was obtained in those samples subjected to more severe and prolonged heat treatments. Similar findings were also reported by Bodor et al [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this line, several authors demonstrated that amitraz was nearly completely degraded within 10 days in honey even at room temperature [ 33 ]. However, it is important to consider that high temperatures increase the HMF levels in honey, which could overcome the set limit by regulation as evidenced in the literature [ 34 ]. The results obtained in this study demonstrated that the different heat treatments tested completely degraded the amitraz and its metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 21 published articles, 3 were reviews [ 2 , 3 , 4 ] and 18 were original research papers [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], that can be roughly separated into 6 categories ( Figure 3 ).…”
mentioning
confidence: 99%
“…The majority of the articles, approximately one third, belongs to the field of applications in agriculture and food science [ 8 , 9 , 12 , 13 , 14 , 21 , 22 ], a field from which aquaphotomics originated, and probably the reason why this category is still at the forefront of aquaphotomics development. Following this category are the preprocessing and chemometrics [ 2 , 4 , 15 , 18 ] and fundamental studies [ 5 , 6 , 10 , 17 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation